Thromboembolic events and antithrombotic prophylaxis in advanced ovarian cancer patients treated with bevacizumab: secondary analysis of the phase IV MITO-16A/MaNGO-OV2A trial. Issue 10 (30th October 2021) - Di Liello, Raimondo; Arenare, Laura; Raspagliesi, Francesco; Scambia, Giovanni; Pisano, Carmela; Colombo, Nicoletta; Frezzini, Simona; Tognon, Germana; Artioli, Grazia; Gadducci, Angiolo; Lauria, Rossella; Ferrero, Annamaria; et al.
Abstract : Introduction: The use of routine antithrombotic prophylaxis is not recommended for advanced cancer patients receiving chemotherapy. The effect of bevacizumab-containing therapy on the risk of thromboembolic events remains controversial in ovarian cancer patients. We report on the incidence of thromboembolic events and the prevalence of antithrombotic therapy in patients enrolled in the single arm, phase IV, MITO-16A/MaNGO-OV2A trial. Methods: In this trial, potential prognostic factors for patients with previously untreated ovarian cancer receiving a combination of platinum-based chemotherapy and bevacizumab were explored and the final analysis has already been reported. In this secondary analysis, the occurrence of thromboembolic events and the use of antithrombotic therapy were described according to the clinical characteristics of the patients. The prognostic role of thromboembolic events for progression-free and overall survival were also evaluated. Results: From October 2012 to November 2014, 398 eligible patients were enrolled. 76 patients (19.1%) were receiving some type of anticoagulant or anti-aggregant treatment at baseline. Overall, 24 thromboembolic events were reported (cumulative incidence of 6.0%). The occurrence of thromboembolic events was not associated with baseline patient characteristics and was not modified by the use of antithrombotic prophylaxis (HR 0.60, 95% CI 0.18 to 2.0). Occurrence of thromboembolic events was not associated with progression-free survival (HR 1.34, 95% CI 0.83 to 2.15) or overall survival (HR 0.78, 95% CI 0.37 to 1.61). Conclusions: In our study, a 6.0% rate of thromboembolic events was reported during treatment with bevacizumab plus chemotherapy. Thromboembolic events were not associated with the clinical characteristics of the patients or with the use of antithrombotic prophylaxis, nor did they significantly affect the long-term prognosis. Trial registration number: NCT01706120